Early development of body representations - Slaughter, Virginia; Brownell, Celia A. (Cambridge studies in cognitive perceptual development, 2012)
"Because we engage with the world and each other through our bodies and bodily movements, being able to represent one's own and others' bodies is fundamental to human perception, cognition and behaviour. This edited book brings together, for the first time, developmental perspectives on the growth of body knowledge in infancy and early childhood and how it intersects with other aspects of perception and cognition. The book is organised into three sections addressing the bodily self, the bodies of others and integrating self and other. Topics include perception and representation of the human form, infant imitation, understanding biological motion, self-representation, intention understanding, action production and perception and children's human figure drawings. Each section includes chapters from leading international scholars drawn together by an expert commentary that highlights open questions and directions for future research"--